PEMILIHAN SOFTWARE ANTIVIRUS UNTUK LABORATORIUM KOMPUTER AKUNTANSI DENGAN METODE AHP ( ANALYTICAL HIERARCHY PROCESS ) - SAPUTRI, SEVTY WAHIDDIRANI (JAK (Jurnal Akuntansi) : Kajian Ilmiah Akuntansi, 2018)
In this globalization era, there are many activities needed technology helps, computertechnology is one of the sample. It's used to ease data operation or searching informationsespecially on learning program in the accounting computer laboratory. According to supportthat process, it's needed to select an antivirus software, to prevent some types of vyrus whichcould absorb the computer system, therefore the computer users will not be annoyed withsome vyrus spreads the computers easily. SMK Jakarta IV nowadays still has some problemsfor getting informations about how to select some kinds of antivirus software such as :Kaspersky Antivirus, Eset Nod32 Antivirus, Avast Antivirus, Avira Antivirus, AVG Antiviruswhich the most effectively to support computer learning at SMK Jakarta IV. This observationuse Analytical Hierarchy Process (AHP) method supported by Expert Choice 2000application program as a media on selecting antivirus program. Based on the observation wehave done, the result is An antivirus software which could help teaching process at school, inthe accounting computer laboratory especially. AVG Antivirus is the right system from thisanalization which could implemented to support learning activities in the accountingcomputer school laboratory at SMK Jakarta IV therefore PC system could be safely protectedfrom the viruses.